Socialization and Training of Basic Gymnastics Skills Based on Sports Science and Technology - Fegie Rizkia Mulyana; Novi Soraya; Iman Rubiana; Melya Nur Herliana (Universitas PGRI Semarang, 2022)
The results of interviews between the service team and the two partners, namely the City Council. PERSANI Tasikmalaya and KKG PJOK SD Kota Tasikmalaya, obtained partner problems, namely coaching and massing the gymnastics branch which was not evenly distributed in each sub-district and PJOK SD teachers had difficulties in teaching basic gymnastic techniques during the learning process. The purpose of this service activity is to provide socialization and training of basic sports science and technology-based gymnastics skills by applying the Android-based GYMBASTECH software as a guide in teaching or practicing basic gymnastics techniques. In addition, it also contributes concepts and ideas to the PERSANI Tasikmalaya City Council in fostering and massing the gymnastics branch in the City of Tasikmalaya through empowering the resources of SD PJOK teachers throughout the city of Tasikmalaya. The implementation method used in this service activity uses the lecture method and socialization by providing theoretical and practical studies related to gymnastics learning strategies and methods in training basic gymnastics skills for four days. The socialization and training began with giving a pretest and ended with a posttest for 45 participants. The results of this service activity are an increase in knowledge and insight as well as the skills of KKG PJOK teachers at SD Kota Tasikmalaya in mastering basic gymnastic skills in terms of pretest results with an average score of 65.97 participants, and posttest results with an average value of 76, 09.Hasil wawancara antara tim pengabdian bersama kedua mitra yaitu Pengkot. PERSANI Tasikmalaya dan KKG PJOK SD Kota Tasikmalaya, didapat permasalahan mitra yaitu pembinaan dan pemassalan cabang olahraga senam yang tidak merata disetiap kecamatan serta guru-guru PJOK SD memiliki kesulitan dalam mengajarkan teknik dasar senam ketika proses pembelajaran. Tujuan dari kegiatan pengabdian ini memberikan sosialisasi dan pelatihan keterampilan dasar senam berbasis IPTEKS keolahragaan dengan mengaplikasikan software GYMBASTECH berbasis android sebagai panduan dalam mengajar ataupun melatih teknik dasar senam. Selain itu memberikan sumbangsih konsep dan gagasan kepada Pengkot PERSANI Tasikmalaya dalam pembinaan dan pemassalan cabang olahraga senam di Kota Tasikmalaya melalui pemberdayaan sumber daya guru PJOK SD se-Kota Tasikmalaya. Metode pelaksanaan yang digunakan dalam kegiatan pengabdian ini menggunakan metode ceramah dan sosialisasi dengan memberikan kajian teoretis dan praktis terkait strategi pembelajaran senam dan metode dalam melatih keterampilan dasar senam selama empat hari. Sosialisasi dan pelatihan diawali dengan memberikan pretest dan diakhiri dengan posttest kepada peserta yang berjumlah 45 orang. Hasil dari kegiatan pengabdian ini yaitu adanya peningkatan pengetahuan dan wawasan serta keterampilan para guru KKG PJOK SD Kota Tasikmalaya dalam menguasai keterampilan dasar senam ditinjau dari hasil pretest dengan nilai rata-rata peserta sebesar 65,97, dan hasil posttest dengan nilai rata-rata 76,09